Analisis Kewenangan Pengadilan Niaga dalam Penyelesaian Kepailitan Asuransi Syariah: Putusan Mahkamah Agung No. 1016 K/Pdt.Sus-Pailit/2016 - Ahmad Ridwan; Mukhlas, Oyo Sunaryo; Sururie, Ramdani Wahyu (Strata Social and Humanities Studies, 2023)
This research analyzes the authority of the Commercial Court in resolving bankruptcy cases of Sharia business institutions with a focus on Supreme Court Decision No. 1016 K/Pdt.Sus-Pailit/2016 highlights legal protection for policyholders and considers Sharia principles in handling these cases. This research uses normative research methods with qualitative analysis. The result of this research is that the Sharia Economic Bankruptcy Settlement Law regulates financial issues in the Sharia economy using Islamic law principles. The process includes handling debts, religious courts, debt restructuring, and protecting creditor rights. This law ensures bankruptcy resolution per Sharia principles, protects creditors' rights, and fulfills financial obligations. Religious courts have jurisdiction, but more explicit regulations regarding handling sharia insurance bankruptcy are still needed. Commercial Court decision regarding the PT case. Mubarakah Sharia Insurance is based on the law, and the bankruptcy requirements are met. Policyholders and legal protection for them are also essential concerns, requiring better supervision, considering the principles of sharia law and justice.